CA 19-9 as a Marker of Survival and a Predictor of Metastization in Cholangiocarcinoma - Coelho,Rosa (2017)
Background: Cholangiocarcinoma is the second most frequent primitive liver malignancy and is responsible for 3% of the malignant gastrointestinal neoplasms. The aims of this study were to determine the association of serum levels of CA 19-9 at diagnosis with other clinical data and serum liver function tests and to identify possible factors that influence the survival rates during follow-up. Methods: Retrospective observational study of 89 patients with a diagnosis of cholangiocarcinoma followed at the Department of Gastroenterology during 5 years. Statistical analyses were performed using SPSS version 20.0. Results: Patients were followed up for a median time of 127 days (IQR: 48-564), and the median age at diagnosis was 71.0 years (IQR: 62.0-77.5). The median survival rate was 14.0 months (IQR: 4.3-23.7), and the mortality rate was 79%. Patients with CA 19-9 levels ≥ 103 U/L had lower albumin levels and higher levels of alanine aminotransferase and γ-glutamyltransferase. CA 19-9 levels ≥ 103 U/L were associated with a higher probability of metastization ( p = 0.001) and lower rates of treatment with curative intent ( p = 0.024). In a multivariate analysis, CA 19-9 levels <103 U/L and surgery were independent predictors of survival. Conclusion: Predictive factors for overall survival were identified, namely presence of metastasis, surgery, and chemotherapy. CA 19-9 levels ≥ 103 U/L were predictive factors for survival and metastization.